Risky Sexual Behavior and Its Determinants among Orphan and Vulnerable Children in Addis Ababa, Ethiopia - Fite, Ayana C.; Cherie, Amsale (Scientific Research, 2016)
Back Ground: Risky sexual behavior among orphans and vulnerable children and its associated physical, psychological and social consequences is becoming a major public health concern globally. Objectives: To assess the prevalence of risky sexual behavior and its determinants among orphan and vulnerable children in Addis Ababa. Methodology: A community based cross sectional study was conducted on three support and care giving organizations for orphans and vulnerable children in Addis Ababa, Ethiopia from March to June 2014. A total of 422 orphan and vulnerable children were selected using systematic sampling. Data were collected using pre tested self-administered questionnaire. Logistic regression was used to analyze the data. Result: A total of 407 (96.4%) respondents participated in this study. Among them 112 (27.5%) had sexual intercourse in their life time, of these 50 (44.6%) started sex before the age of 15, 94 (83.9%) had forced sex, 84 (75.0%) had multiple sexual partners, only 16 (14.3%) used condom the first time they had sex and 96 (85.7%) participated in transactional sex. Females were about 3.25 (2.67 - 7.3) times more likely to engage in risky sexual behavior than male respondents, double orphans had 4.32 (2.45 - 9.54) odds of risky sexual behavior compared to their counterparts. Those respondents who had knowledge of HIV transmission and prevention were less likely to be involved in risky sexual behavior 0.58 (0.41 - 0.93). Conclusion: Orphan and vulnerable children are at a higher likelihood of risky sexual behavior. Intervention targeted at multilevel such as orphan survival training, assertive communication skills, sexuality education and education about HIV risk perception, physical, psychological and human right protection, social support, and economic access for basic needs need to be given consideration.
Keywords: Orphan; Vulnerable Children; Risky Sexual Behavior; Forced Sex; Transactional Sex; Addis Ababa